Wizards of waverly place locker of secrets (London : Parragon, 2010)
Wizards of Waverly Place: The Movie is a 2009 Disney Channel movie about Alex Russo, a young wizard who accidentally casts a spell that puts her family in jeopardy
Keywords: Fantasy - comedy